Valuation of banks in emerging markets: an exploratory study - Sabilika, Keith (Rhodes University, Faculty of Commerce, Department of Management, 2014)
Practitioners and academics in emerging markets are yet to agree on how best they can value companies in emerging markets. In contrast, academics and practitioners in developed markets seem to agree on mainstream valuation practices (Bruner, Eades, Harris and Haggins, 1998; Graham and Harvey, 2001). This study was therefore aimed at achieving such consensus with particular attention being paid to the emerging market banks. Emerging market banks are by no means small and are growing fast. Furthermore, these banks are currently involved in lots of cutting age economic activities such as mergers and acquisitions (M&A), joint ventures and strategic alliances which require sound valuation practices that are based on empirical evidence. The primary purpose of this research was to establish consensus of opinion among experts with regard to the valuation of banks in emerging markets. To achieve the purpose of this study the Delphi technique, which is a structured survey method that relies on a panel of experts to answer questionnaires in two or more Delphi rounds, was used to gather data and develop consensus among experts (Kalaian and Kasim, 2012). The main findings in this study pertain to aspects concerning the type of analysis considered by experts when analysing the performance of banks, how experts compare the discounted cash flow (DCF) approach to multiples valuation approach, the challenges encountered by experts when valuing banks in emerging markets, and how experts compute the cost of capital for banks in emerging markets. The main findings of this study can be summarised as follows: ∙ When analyzing the performance of banks, it is essential to conduct a bank-specific, industry and macroeconomic analysis; ∙ When estimating the future performance of banks, the time series analysis and an explicit forecast period of between 4-10 years may be used; ∙ When estimating the terminal value for banks in emerging markets, the perpetuity with growth is used; ∙ When computing the value for banks, the DCF valuation approach (equity DCF and DDM valuation models) are used as primary valuation methods and the relative valuation approach (P/E and P/BV ratio) are used as secondary valuation methods; ∙ The DCF valuation approach is considered as more accurate and popular when valuing banks in emerging markets; and ∙ When estimating the cost of equity, the capital asset pricing model (CAPM) is used.
Keywords: Banks and banking -- Valuation; Banks and banking -- Valuation -- Developing countries; Discounted cash flow; Capital assets pricing model; Capital -- Developing countries